2007
DOI: 10.1159/000101473
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Predictors of Improvements in Adults’ Spoken Word Recognition Six Months after Cochlear Implant Activation

Abstract: This study investigated whether cognitive measures obtained prior to cochlear implant surgery activation could predict improvements in spoken word recognition in adult cochlear implant recipients 6 months after activation. In addition to noncognitive factors identified by previous studies (i.e. younger age, shorter duration of hearing loss), the present results indicated that improvement in spoken word recognition was associated with higher verbal learning scores and better verbal working memory. Contrary to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
110
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(130 citation statements)
references
References 68 publications
(37 reference statements)
12
110
2
3
Order By: Relevance
“…Haumann et al (2010) found that postoperative speech intelligibility prediction in CI users using a weighted summed correlation procedure was improved when the TRT test results were included. This is also in line with Heydebrand et al (2007), who documented the importance of cognitive variables, e.g., verbal learning, to the outcome, and thus may explain part of the remaining prediction variance. Consequently, the internal noise could possibly be fitted as a function of the TRT test or other cognitive test results.…”
Section: Individual Fitting Of Model Parameterssupporting
confidence: 89%
“…Haumann et al (2010) found that postoperative speech intelligibility prediction in CI users using a weighted summed correlation procedure was improved when the TRT test results were included. This is also in line with Heydebrand et al (2007), who documented the importance of cognitive variables, e.g., verbal learning, to the outcome, and thus may explain part of the remaining prediction variance. Consequently, the internal noise could possibly be fitted as a function of the TRT test or other cognitive test results.…”
Section: Individual Fitting Of Model Parameterssupporting
confidence: 89%
“…This view of working memory and category learning closely resembles what has been argued in speech, in which listeners must shift attention to diagnostic cues while filtering out information that is not diagnostic for learning (Nusbaum & Schwab, 1986). Indeed, working memory has been shown to predict the efficacy of understanding cochlear implant (CI) speech in both children (Fagan, Pisoni, Horn, & Dillon, 2007) and adults (Heydebrand, Hale, Potts, Gotter, & Skinner, 2007). CI speech is inherently a perceptual learning task, as individuals must learn to remap their acoustic-to-phonetic categories onto degraded speech sounds.…”
Section: Discussionmentioning
confidence: 52%
“…A limited number of studies examined whether lipreading ability may contribute to cochlear implant outcome. In a multivariate analysis including 37 adult patients (mean age: 54 years; range: 24-80), Heyderbrand et al [2007] reported that lipreading is strongly correlated with age, and that verbal learning and lipreading account for 72% of the variance in word recognition in quiet observed at 6 months. Behavioral and brain imaging studies demonstrate a cross-modal reorganization of the visual and auditory strategies induced by deafness.…”
Section: Discussionmentioning
confidence: 99%